Are indexed values better for defining exercise pulmonary hypertension?. Issue 3 (9th September 2017) - Weatherald, Jason; Boucly, Athénaïs; Lau, Edmund; Godinas, Laurent; Savale, Laurent; Jaïs, Xavier; Montani, David; Sitbon, Olivier; Simonneau, Gérald; Humbert, Marc; Chemla, Denis; Hervé, Philippe
Pulmonary hypertension (PH) is defined by resting mean pulmonary arterial pressure (mPAP) ≥25 mmHg [1]. Patients with pulmonary vascular disease (PVD) or left heart disease (LHD) may demonstrate abnormal haemodynamic responses to exercise even when resting mPAP is normal [2]. After the 4th World Symposium on PH in 2008, exercise PH, defined as mPAP >30 mmHg during exercise, was abandoned due to a lack of supportive evidence and the observation that mPAP frequently exceeds 30 mmHg in healthy individuals who attain high cardiac output (CO) [3, 4]. A disproportionate increase in mPAP relative to CO during exercise, however, reflects either an increase in pulmonary vascular resistance (PVR), as in PVD, or elevated left ventricular filling pressure in LHD. Therefore, attention to the mPAP/CO relationship, such as the mPAP/CO slope or the total pulmonary resistance (TPRmax ) >3 Wood units (WU) at maximal exercise, could refine the definition of an abnormal haemodynamic response to exercise in order to reduce false positive diagnoses [5–7]. Indeed, combining mPAP (mPAPmax ) >30 mmHg and the TPRmax >3 WU at maximal exercise has been demonstrated to have high accuracy in discriminating patients with PVD or LHD and resting mPAP ≤20 mmHg from controls or healthy volunteers [7]. Furthermore, these criteria have superior diagnostic performance compared to either the mPAP/CO slope or change in mPAP/CO during exercise [8]. No advantage to using indexed total pulmonary resistance in the definition of exercise pulmonary hypertension http://ow.ly/tmgi30dMN5T